Long-Acting Glucagon-Like Peptide-1 Receptor Agonists Suppress Voluntary Alcohol Intake in Male Wistar Rats - Marty, Vincent N.; Farokhnia, Mehdi; Munier, Joseph J.; Mulpuri, Yatendra; Leggio, Lorenzo; Spigelman, Igor (Frontiers in Neuroscience, 2020)
Alcohol use disorder (AUD) is a chronic relapsing condition characterized by compulsive alcohol-seeking behaviors, with serious detrimental health consequences. Despite high prevalence and societal burden, available approved medications to treat AUD are limited in number and efficacy, highlighting a critical need for more and novel pharmacotherapies. Glucagon-like peptide-1 (GLP-1) is a gut hormone and neuropeptide involved in the regulation of food intake and glucose metabolism via GLP-1 receptors (GLP-1Rs). GLP-1 analogues are approved for clinical use for diabetes and obesity. Recently, the GLP-1 system has been shown to play a role in the neurobiology of addictive behaviors, including alcohol seeking and consumption. Here we investigated the effects of different pharmacological manipulations of the GLP-1 system on escalated alcohol intake and preference in male Wistar rats exposed to intermittent access 2-bottle choice of 10% ethanol or water. Administration of AR231453 and APD668, two different agonists of G-protein receptor 119, whose activation increases GLP-1 release from intestinal L-cells, did not affect voluntary ethanol intake. By contrast, injections of either liraglutide or semaglutide, two long-acting GLP-1 analogues, potently decreased ethanol intake. These effects, however, were transient, lasting no longer than 48 hours. Semaglutide, but not liraglutide, also reduced ethanol preference on the day of injection. As expected, both analogues induced a reduction in body weight. Co-administration of exendin 9-39, a GLP-1R antagonist, did not prevent liraglutide- or semaglutide-induced effects in this study. Injection of exendin 9-39 alone, or blockade of dipeptidyl peptidase-4, an enzyme responsible for GLP-1 degradation, via injection of sitagliptin, did not affect ethanol intake or preference. Our findings suggest that among medications targeting the GLP-1 system, GLP-1 analogues may represent novel and promising pharmacological tools for AUD treatment.